2020
DOI: 10.1016/j.scs.2020.102475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contexts in urban residential areas on the pleasantness and appropriateness of natural sounds

Abstract: Before introducing natural sounds to potentially improve the soundscape quality, it is important to understand how key contextual factors (i.e. expected activities and audiovisual congruency) affect the soundscape in a given location. In this study, the perception of eight natural sounds (i.e. 4 birdsongs, 4 water sounds) at five urban recreational areas under the constant influence of road traffic was explored subjectively under three laboratory settings: visual-only, audio-only, and audio-visual. Firstly, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…Unlike Hong et al's research, outdoor activities have a positive influence on older people's preferences for natural sounds. 15 Similar to the results from Mu et al's study, 17 most people also prefer a quiet outdoor environment, and their acoustic comfort is influenced by sound preferences. Additionally, the type of activity also affected older people's needs in evaluating outdoor soundscapes.…”
Section: Outdoor Acoustic Needssupporting
confidence: 76%
See 1 more Smart Citation
“…Unlike Hong et al's research, outdoor activities have a positive influence on older people's preferences for natural sounds. 15 Similar to the results from Mu et al's study, 17 most people also prefer a quiet outdoor environment, and their acoustic comfort is influenced by sound preferences. Additionally, the type of activity also affected older people's needs in evaluating outdoor soundscapes.…”
Section: Outdoor Acoustic Needssupporting
confidence: 76%
“…14 They also studied the impact of outdoor activities on the acoustic perception of 50 participants and found that outdoor activities (relaxation, outdoor entertainment, and social gathering) had no influence on enhancing satisfaction obtained from natural sounds. 15 However, most studies on the soundscape of older people focus on the indoor environment. Wang and Kang investigated the soundscape in nursing homes and found that rather than reducing the sound of music or of other activities, such as table tennis, older people preferred reducing the sound of chatter.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies ( Kang, 2006 ; Nilsson & Berglund, 2006 ; Park, Lee, Jung, & Swenson, 2020 ) have demonstrated that sound has an important role in the perception of built environments. In particular, natural sounds were a significant factor in enhancing the acoustic comfort and sustainability of the environments ( Hong et al, 2020 ; Hong, Wang, Liu, & Lan, 2019 ; Truax, 2019 ). Thus, it is necessary to examine people’s reactions to noises during the lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…In healthcare environments, Mackrill et al proposed an emotional-cognitive framework for a qualitative perceptual assessment of hospital 'soundscapes' to help understand perceptual effects beyond reduced sound levels [21][22][23][24][25]. It was acknowledged that the framework was developed in the absence of context, a critical factor in one's perception of the complex acoustical environment [26,27].…”
Section: Assessment Of Hospital Acousticsmentioning
confidence: 99%